2020
DOI: 10.1177/1078155220937751
|View full text |Cite
|
Sign up to set email alerts
|

Topical aloe vera for the treatment of cetuximab-related acneiform rash in colorectal cancer: A case report

Abstract: Introduction Colorectal cancer is one of the most common cancers in the world. Cetuximab is an epidermal growth factor receptor (EGFR) inhibitor which provides survival benefit when combined with chemotherapy in RAS wild type metastatic colorectal cancer. Cutaneous toxicities associated with cetuximab have a significant impact on patient quality of life, treatment continuation and healthcare resource utilization. Case report Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Several studies have investigated the biological and toxicological properties of Aloe Vera and have proved to have anti-diabetic activity 22 , cell proliferation property, angiogenesis, immune-modulatory, antimicrobial 23 , anti-cancer properties 24 and various skin diseases 25 . An acute toxicity study done on Aloe Vera gel dosed water showed no signs of toxicity at 500mg/kg 26 .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have investigated the biological and toxicological properties of Aloe Vera and have proved to have anti-diabetic activity 22 , cell proliferation property, angiogenesis, immune-modulatory, antimicrobial 23 , anti-cancer properties 24 and various skin diseases 25 . An acute toxicity study done on Aloe Vera gel dosed water showed no signs of toxicity at 500mg/kg 26 .…”
Section: Discussionmentioning
confidence: 99%
“…Many other treatment and prophylactic measures exist; nevertheless, further research is required as they currently do not possess enough data that would support their efficacy in practice. These include topical aloe vera gel, topical vitamin K1 (phytonadione), Huang-Lia Jie-Du decoction, epidermal growth factor-containing topical creams, and dapsone [4, 5, 12, 13]. In addition to the lack of sufficient evidence to support them, some of them, such as vitamin K1 and retinoids, have been shown to have undesirable side-effects [4].…”
Section: Introductionmentioning
confidence: 99%